Metacarpal Bone Density in Carpal Tunnel Syndrome Patients Without Thenar Atrophy - Serpil Savaş; Berna Okudan; Hasan Rifat Koyuncuoğlu; Hakan Çelik; Tamer Karaaslan; Mustafa Yıldız (Archives of Rheumatology, 2007)
Objective: Bone loss due to thenar atrophy was reported in the metacarpal bones in premenopausal patients with carpal tunnel syndrome (CTS). The present study was designed to assess bone density in the metacarpal bones in patients with CTS without thenar atrophy and to correlate the metacarpal bone density with the electrophysiological findings, hand strength and Boston Questionnaire (BQ). Patients and Methods: Thirty premenopausal patients with CTS without thenar atrophy were enrolled in this study. Thirty-two consecutive premenopausal women were included in the study as controls. The severity of symptoms and the functional status of CTS patients were assessed with Boston Questionnaire (BQ). Muscle strength of both hands was tested first with a Jamar dynamometer followed lateral pinch using a manual pinch meter in both groups. Bone mineral density (BMD) was measured by dual energy X-ray absorptiometry (DXA) at the second to fourth metacarpal bones of right hand. Electrodiagnostic testing was performed in CTS group. Results: BMD values at the metacarpal bones did not differ between the CTS group and controls (0.49±0.07 gr/cm2 vs 0.50±0.07 gr/cm2 respectively, p>0.05). Hand grip strength (23.98± 5.50 kg vs 23.88±3.76 kg respectively, p>0.05) and lateral pinch strength (6.70±1.44 vs 6.99±1.17 kg respectively, p>0.05) of CTS group and controls was similar. Electrophysiological findings, hand strength and BQ were not correlated with the bone density at the metacarpal bones in patients with CTS without thenar atrophy (p>0.05). Conclusion: Thenar atrophy seems be the most important predicting factor for the low bone density at the metacarpal region in patients with CTS. (Rheumatism 2007; 22: 15-9)